2D phosphorene as a water splitting photocatalyst: fundamentals to applications. Issue 3 (26th January 2016) - Rahman, Mohammad Ziaur; Kwong, Chi Wai; Davey, Kenneth; Qiao, Shi Zhang
Abstract : In this review, we focus on analysing the fundamental electronic, optical and chemical properties of 2D phosphorene to assess its suitability as a metal-free water splitting photocatalyst. Abstract : Hydrogen from direct splitting of water molecules using photons is reckoned to be a sustainable and renewable energy solution for the post fossil-fuel era. Efficient photocatalysts, including metal-free photocatalysts, are key determinants of cost-effective hydrogen generation at a large-scale. The search for new materials that are metal-free is therefore ongoing. Recently, 2D phosphorene, a phosphorus analogue of graphene, has been added as a new semiconductor to the family of monolayer-flatland materials. In this review, we focus on analysing the fundamental electronic, optical and chemical properties of 2D phosphorene and assess its suitability as a metal-free water splitting photocatalyst. We also critically analyse its stability against claims from environmental antagonists and attempt to predict its future as a photocatalyst. This review provides timely information for researchers, scientists and professionals devoted to materials research for photocatalysis.